USP6-associated soft tissue tumors with bone metaplasia: Clinicopathologic and genetic analysis and the identification of novel USP6 fusion partners - Zhang, Yahan; Qiu, Yan; Zhang, Xianliang; He, Xin; Chen, Chen; Chen, Min; Zhang, Hongying (Frontiers in Oncology, 2023)
Introduction Among those tumors with consistent USP6 rearrangement, some arise from soft tissue and show bone metaplasia, including myositis ossificans (MO), fibro-osseous pseudotumor of digits (FOPD), soft tissue aneurysmal bone cyst (ST-ABC) and fasciitis ossificans (FO). These lesions are easily confused with malignancies because they show a rapid growth rate and brisk mitoses. Here, we aim to clarify the clinicopathologic and genetic characteristics of this entity and analyze the correlations among the different subtypes in one of the largest cohorts. Materials and Methods The clinicopathologic features of 73 cases of MO, FOPD, ST-ABC and FO diagnosed at West China Hospital, Sichuan University from January 2010 to December 2021 were retrospectively analyzed. Forty-three undecalcified samples were analyzed by systematic genetic studies, including fluorescence in situ hybridization (FISH), reverse transcription polymerase chain reaction (RT-PCR), Sanger sequencing and next-generation-based sequencing were performed. Results This series included 40 males and 33 females aged 2 to 80 years old (median: 31 years). FOPD occurred in extremal soft tissue, while lower extremities (38/58, 65.5%) were the most commonly involved lesions in the other three subgroups. Histologically, proliferative myofibroblasts/fibroblasts with varying degrees of osteoid tissue were present. Fluorescence in situ hybridization (FISH) results indicated that 22 cases (22/27, 81.5%) were positive for USP6 rearrangement, and 5 cases were negative. Among those cases with positive FISH results, 18 underwent reverse transcription-polymerase chain reaction (RT-PCR) detection that successfully detected common USP6 fusion types. Thirteen cases showed COL1A1::USP6 fusion, one showed MYH9::USP6 fusion, and 4 were negative for common fusion types. Next-generation-based sequencing technology was performed on two lesions with negative RT–PCR results and novel fusion partners SNHG3 and UBE2G1 were discovered. Conclusions Our findings revealed that COL1A1 is the most common fusion partner in this entity, unlike primary aneurysmal bone cysts and nodular fasciitis. Notably, we believed that FO may demonstrate more similar clinicopathologic and genetic manifestations with MO/FOPD and ST-ABC instead of nodular fasciitis for involving lower limbs most frequently and showing recurrent COL1A1::USP6 fusion. Additionally, this study also found two novel USP6 fusion partners, which further expanded our knowledge of this neoplastic spectrum.